Megaliths of the World VOLUME 1 (Volume 1) - Laporte, Luc (Archaeopress Publishing, 2022)
"Megaliths of the World brings together the latest research on megalithic monuments throughout the world. Many of these sites are well known, others less familiar, yet equally deserving of close attention. Megalithic monuments in different regions of the world are far from being a single unified phenomenon, having varied chronologies, and diverse origins, but they all share a certain family resemblance through their common characteristic: the deployment of large stones. No fewer than 150 researchers have contributed 72 articles and inserts, providing a vital region-by region account of the megalithic monuments in their specialist areas, and the current state of knowledge. The insights offered in these volumes emphasize the particular character and significance of these apparently inanimate stones. The use of such large blocks must surely have been an expression of power or prestige, yet the size and materiality of the stones themselves opens up new perspectives into the meaning and symbolism of these monuments, the places from which the blocks were derived, and the way they were manipulated and shaped. Megaliths of the World takes the reader on a fascinating journey, offering new insights through encounters with megaliths and megalithic traditions that will often be new and unfamiliar. Highlighting salient themes, it provides a compendium of detailed information that will be vital to anyone interested in the phenomenon of megalithic monumentality."